Improved capacitance of nitrogen-doped delaminated two-dimensional titanium carbide by urea-assisted synthesis. (20th January 2017) - Yang, Chenhui; Que, Wenxiu; Yin, Xingtian; Tian, Yapeng; Yang, Yawei; Que, Meidan
Abstract: Two-dimensional transition metal carbides (MXenes) were recently emerged as promising electrode materials for energy storage applications. Herein, we report a high-capacity supercapacitor material based on nitrogen-doped delaminated titanium carbides (N-d-Ti3 C2 ) synthesized through the facile urea-assisted delamination of large-scale Ti3 C2 and carbonization of delaminated Ti3 C2 (d-Ti3 C2 ) mixed with urea. The two-dimensional N-d-Ti3 C2 nanosheets exhibit a high specific capacitance of 266.5 F g −1 at the scan rate of 5 mV s −1 in 6 M KOH electrolyte solution, with a high capacitance retention capability. This new type of nitrogen-doped delaminated titanium carbide could be a promising electrode material for high-performance supercapacitors.